VD_FINDINFO Jug / 2023 / 493 vom 15. Mai 2023 - VD Tribunal cantonal (2023)
EXPULSIONDROIT PÉNAL, LÉSION CORPORELLE GRAVE, TENTATIVEDROIT PÉNAL, REJET DE LA DEMANDE | 106 CP, 22 ad 122 CP, 40 CP, 47 CP, 51 CP, 66a al. 1 let. b CP, 69 CP, 19a ch. 1 LStup